Lasting immune memory against hepatitis B in children after primary immunization with 4 doses of DTPa-HBV-IPV/Hib in the first and 2.sup.nd .sup.year of life - Steiner, Michael; Ramakrishnan, Gunasekaran; Gartner, Britta; Van Der Meeren, Olivier; Jacquet, Jeanne-Marie; Schuster, Volker (BMC infectious diseases, 2010)
Few studies have assessed long term persisting immunity against hepatitis B virus (HBV) in children vaccinated during infancy with combined vaccines containing recombinant HBV surface antigen (HBs). We assessed antibody persistence and immune memory in children 4-5 years of age, previously vaccinated with four doses of combined hexavalent DTPa-HBV-IPV/Hib vaccine (Infanrix hexa[TM]). Immune memory was assessed in 301 children through administration of a challenge dose of monovalent HBV vaccine. At 4-5 years of age, 85.3% of subjects had persisting anti-HBs antibody concentrations [greater than or equal to] 10 mIU/mL, rising to 98.6% after the HBV challenge dose. All but 12 subjects (95.8%) achieved post-challenge anti-HBs concentrations [greater than or equal to] 100 mIU/mL. The post-challenge anti-HBs GMC rose by 100-fold compared to pre-challenge concentrations. An anamnestic response to the HBV vaccine challenge was observed in 96.8% of subjects, including 17/21 (81.0%) of children with initially undetectable antibodies ([less than]3.3 mIU/mL). All but 4 of 42 subjects (90.5%) with anti-HBs antibodies [less than]10 mIU/mL prior to the challenge dose, achieved seroprotective levels afterwards. A 4-fold rise in antibody concentration after the challenge dose was observed in 259/264 (98.1%) of initially seropositive subjects. The magnitude of the post-challenge responses was proportional to pre-challenge anti-HBs levels. No serious adverse events were reported during the study. The combined DTPa-HBV-IPV/Hib vaccine induced lasting immune memory against hepatitis B. Long term protection afforded by DTPa-HBV-IPV/Hib is likely to be similar to that observed following priming with monovalent HBV vaccines.